2022
DOI: 10.3390/microorganisms10050886
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Evidence for the Role of Botulinum Neurotoxin A (BoNT/A) in the Treatment of Peripheral Nerve Injury

Abstract: Traumatic peripheral nerve injuries tend to be more common in younger, working age populations and can lead to long-lasting disability. Peripheral nerves have an impressive capacity to regenerate; however, successful recovery after injury depends on a number of factors including the mechanism and severity of the trauma, the distance from injury to the reinnervation target, connective tissue sheath integrity, and delay between injury and treatment. Even though modern surgical procedures have greatly improved th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 147 publications
0
6
0
Order By: Relevance
“…Franz et al reported the effects of BoNT/A preconditioning on reinnervation [ 16 ]. Adlet et al suggested that BoNT/A may accelerate nerve regeneration by improving blood flow and upregulating angiogenesis [ 17 ]. A study by Finocchiaro et al describes that mast cells and macrophages are further activated to speed up the removal of myelin debris and promotes nerve regeneration after BoNT/A injection [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Franz et al reported the effects of BoNT/A preconditioning on reinnervation [ 16 ]. Adlet et al suggested that BoNT/A may accelerate nerve regeneration by improving blood flow and upregulating angiogenesis [ 17 ]. A study by Finocchiaro et al describes that mast cells and macrophages are further activated to speed up the removal of myelin debris and promotes nerve regeneration after BoNT/A injection [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…We focused on the role of Schwann cells in peripheral nerve regeneration. Nerve regeneration is predominantly linked to enhanced Schwann cell proliferation, transformation to the repair phenotype, and mast cell and macrophage activation [ 17 ]. Spinal glial cell activation and the consequent release of pro-inflammatory factors can be inhibited by BoNT/A [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, botulinum toxin has been used to alleviate pain and dystonia simultaneously, particularly musculoskeletal pain and lower back pain ( 17 ). In addition to reducing abnormal muscle contraction by inhibiting the release of acetylcholine at the neuromuscular junction, this toxin may relieve neuropathic pain through other mechanisms, such as improving blood supply ( 18 ), reducing pain-related mediators, and inhibiting central perception ( 17 ). In the patient mentioned in our study, botulinum toxin successfully inhibited the dystonia during the later period of treatment but failed to relieve pain, potentially because this patient's neuropathic pain both preceded the dystonia and extended beyond the area of severe muscle spasm.…”
Section: Discussionmentioning
confidence: 99%
“…23 BoNT-A can accelerate nerve regeneration and improve functional recovery after injury to peripheral nerves. 12 Moreover, BoNT-A has the capacity to promote wound healing by attenuating the release of norepinephrine and many neurotransmitters, which inhibit vasoconstriction and increase blood flow and, in this way, may exert some positive effects on chronic ulcers. Ischemic ulcers, secondary to Raynaud’s phenomenon, seem to be the most likely type of ulcers that have benefited from BoNT-A.…”
Section: Discussionmentioning
confidence: 99%
“…Results from recent studies in animal models suggest that botulinum neurotoxin A (BoNT-A) can accelerate nerve regeneration and improve functional recovery after injury to peripheral nerves, with the possible mechanisms proposed for such effects being activation or proliferation of support cells (Schwann cells, mast cells, and macrophages), increased angiogenesis and enhanced blood flow to regenerating nerves. 12 With regard to its effects on pain, some possible mechanisms of BoNT-A include retrograde axonal transport of toxins, inhibition of neuropeptides, such as substance P and calcitonin gene-related protein (CGRP), glutamate and deactivation of Na channels. 13 …”
Section: Introductionmentioning
confidence: 99%